مدى استجابة مكاتب المراجعة في إعداد تقرير مراجعة حسابات المؤسسة الاقتصادية حسب معيار المراجعة الدولي 700 تكوين رأي وإعداد تقرير مراجعة القوائم المالية - دراسة عينة من المهنيين والأكادميين في الجزائر العاصمة - بن دغي, محمد ياسين; بوعريوة, الربيع (جامعة الوادي - University of Eloued, 2023)
يعتبر تقرير مراجعة حسابات المؤسسة الاقتصادية الصادر من طرف مكاتب المراجعة من أهم النقاط الختامية للإدلاء بالراي المحايد والملخص لعدة اجراءات تنظيمية وتحليلية مفادها بلورة الصورة الصادقة للمركز المالي للمؤسسة الاقتصادية. وإعطاء ضمانات كافية سواءا كان ذلك بالنسبة للملاك الدائمين والمستثمرين عن طريق الإكتتاب أو بالنسبة الأخرى للمتعاملين الاقتصاديين الخارجيين بما في ذلك مؤسسات الدولة - الزبائن، الموردون. لدى وجب على الباحثان تقديم خصائص وإجراءات إعداد وكتابة تقرير مراجعة الحسابات حسب ما يتضمنه معیار مراجعة الدولي رقم 700 تكوين رأي وإعداد تقرير مراجعة البيانات المالية، في شكل دراسة حالة على عينة من المهنيين والاكادميين في الجزائر العاصمة. The report of the audit of the account of the economicinstitutions used by the audit offices is considered one of the most important concluating pointe for expressing the neutral opinion and summarizing a number of organizational and defining pader procedures that crystallized the true picture of the financial position of the economic institution, and giving sufficient guarantees, whether in relation to permanent owners and investore through subscription, or in relation to other external economic dealers, including state institution customers and suppliers. The researchers must present the characteristics and procedures for preparing and writing the audit report according to what is included in the International Standard on Auditing 700, forming an opinion and preparing the financial statements audit report, in the form of a case study on a sample of professionals and academics in Algiers.
The extent of the response of the audit offices in preparing report of the accounts of the economic institution accounting to the international auditing Standard 700, preparing the frorming an opinion and audit report of the financial statements -a study of a sample of professionals in Algiers
مقال
Keywords: مكاتب المراجعة ; البيانات المالية ; المؤسسة الاقتصادية ; معيار المراجعة الدولي 700 ; تقرير المراجعة المالية; : Acadit offices, financial statements, economic institution, ISA 700,Financial revien